Student engagement and motivation in a digital environment - Tonenchuk, Tetiana (National University of Urban Economy in Kharkiv, Tesol-Ukraine. Kharkiv, 2021)
Shifting to the digital format of communication and learning raises some issues: how to engage and motivate students to participate, how to keep students’ attention, how to make the process as effective and authentic as face-to-face teaching and how to maximize presence feeling while teaching in a digital format. Though it looks as a rather challenging task to motivate and engage learners when teaching online, innovative instructional methods and modern technologies can give a break from traditional activities through immersion into the foreign language environment, they are learner-centered and largely appreciated by students.
частина монографії
Keywords: digital learning; eLearning; remote teaching; motivation; learning in a digital environment; student engagement